2017
DOI: 10.1590/0103-8478cr20160344
|View full text |Cite
|
Sign up to set email alerts
|

Zeolites in poultry and swine production

Abstract: Zeolites are minerals that have intriguing properties such as water absorption, ion adsorption and cation exchange capacity. There are approximately 80 species of natural zeolites recognized and hundreds of artificial zeolites, which have been researched in several fields. Due to their chemical characteristics, zeolites have great potential for use in animal production, especially in poultry and swine farms, as food additives, litter amendment and treatment of residues, with direct and indirect effects on perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…In addition, similar beneficial effects have also been observed in other farm animals such as pigs and poultry. In this regard, ZC has shown a positive effect in farmed poultry in balancing the total intestinal microbial flora, reducing toxic effects of aflatoxins and increasing the antioxidant activity (see below) of peroxidase, catalase, and SOD (superoxide dismutase) as well as increasing levels of omega-3 fatty acids in eggs [56,57,58]. The physical–chemical properties and therefore detoxifying abilities improve when ZC is subjected to PMA technology as observed in some clinical settings.…”
Section: Zeolite Clinoptilolite: a Multifaceted Rockmentioning
confidence: 99%
“…In addition, similar beneficial effects have also been observed in other farm animals such as pigs and poultry. In this regard, ZC has shown a positive effect in farmed poultry in balancing the total intestinal microbial flora, reducing toxic effects of aflatoxins and increasing the antioxidant activity (see below) of peroxidase, catalase, and SOD (superoxide dismutase) as well as increasing levels of omega-3 fatty acids in eggs [56,57,58]. The physical–chemical properties and therefore detoxifying abilities improve when ZC is subjected to PMA technology as observed in some clinical settings.…”
Section: Zeolite Clinoptilolite: a Multifaceted Rockmentioning
confidence: 99%
“…Clinoptilolite has been used for many decades as a feed additive in animal husbandry [ 27 ]; its growth promoting effect is thought to arise–at least in part–from binding of mycotoxins [ 29 ]. Livestock are fed clinoptilolite for months to years without obvious adverse events [ 46 , 47 ]. Hence, it is safe to posit that clinoptilolite is innocuous, in particular if contaminating heavy metals have been removed from its crystal lattice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this improvement in semen quality might be due to the capability of free silicate anions in the zeolite structure to make electrolyte balance in the liver, kidneys, testes and blood (Kleiner et al, 2001 andTas et al, 2007). Zeolite, being ionexchangers, participate in certain biochemical transformations, including the transport, activation and prolongation of enzyme and hormone action, maintain ion balance in terms of calcium and sodium, stabilize and regulate the soda-and-acid reserves in the gastrointestinal tract, normalize the homeostasis (inner medium) of animals, increase the nutrient conversion (Schneider et al, 2017). It has been reported that testis degenerations were formed in mineral excess by means of suppression of gonadotropin excretion (Amal, Hasan, 2013).…”
Section: Semen Qualitymentioning
confidence: 99%
“…Also, zeolite, being the adsorbents, eliminates a number of toxic substances (heavy metal salts, nitrates, nitrites, mycotoxins, radionuclides, metabolism products) from the organism. Zeolite, being ion-exchangers, participate in certain biochemical transformations, including the transport, activation and prolongation of enzyme and hormone action, maintain ion balance in terms of calcium and sodium, stabilize and regulate the soda-and-acid reserves in the gastrointestinal tract, normalize the homeostasis (inner medium) of animals, increase the nutrient conversion (Schneider et al, 2017). In addition, zeolite improves the nutrients conversion in poultry under unfavorable conditions (Andronikashvili et al, 2009).…”
mentioning
confidence: 99%